Collections, information and computers in the National Museums of Scotland - Burnett, John (Proceedings of the Society of Antiquaries of Scotland, 1992)
Presents some history of collecting and classification of information in the National Museums of Scotland and suggests likely developments made possible by recent computerised listing of the collections.